Gradient heterostructured laser-powder bed fusion processed CoCrFeMnNi high entropy alloy - Karthik G.M.; Kim Y.; Kim E.S.; Zargaran A.; Sathiyamoorthi P.; Park J.M.; Jeong S.G.; Gu G.H.; Amanov A.; Ungar T.; Kim H.S. (My University, 2025)
Developing metal additive parts with a synergy in strength and ductility is a demanding need for many critical applications. Recently, gradient structures have been of research interest as it facilitates intrinsic synergetic strengthening. In the current work, gradient microstructures are obtained on laser-powder bed fusion processed (LPBF) CoCrFeMnNi high entropy alloy using ultrasonic nanocrystal surface modification (UNSM). The UNSM treatment resulted in a thin layer of gradient microstructures with a gradient in dislocation density, twin fraction, and grain size on the surface of the LPBF samples. The gradient microstructures led to gradient properties and contributed significantly to hetero deformation-induced (HDI) strengthening. Further, a comparison with the wrought counterparts, which showed higher HDI stresses and strain hardening than the LPBF samples, establishes the need for a substantial strength difference between the hard UNSM-affected region and the soft unaffected region for significant HDI strengthening. Moreover, in the current work, a dislocation-based constitutive model is developed to represent the deformation mechanism of the gradient structured sample and is validated with the experimental results. © 2022 Elsevier B.V.